The Relationship between R&D Expenditures and Economic Growth in BRICS-T Countries - Bayraktar, Yüksel; Dündar, Necip; Özyılmaz, Ayfer (Eskisehir Osmangazi Univ, Fac Education, 2022)
R&D, which is one of the main determinants of technological development, has a critical role in determining the development differences between countries. The fact that developing countries as well as developed countries start to allocate more funds to R&D expenditures causes the literature on this subject to remain up-to-date. The aim of this study is to examine the relationship between R&D expenditures and growth in the period of 2000-2018 in Brazil, Russia, India, China, South Africa, and Turkiye (BRICS-T). In this context, Dumitrescu-Hurlin's (2012) causality test, Impulse-Response and Variance Decomposition analyzes are used together with the panel VAR approach. According to Dumitrescu-Hurlin (2012) causality test, there is a bidirectional causality relationship between R&D expenditures and growth in BRICS-T countries
Keywords: R& D Expenditure; Growth; Panel VAR; BRICS-T; Innovation; Productivity; Causality; Model